Analisis Faktor Yang Mempengaruhi Kualitas Laporan Keuangan (BLUD) Puskesmas Pada Pemerintah Kota Pekanbaru - Ricardo, Ricardo; Trisna, Wen Via; Astika, Fitriani (Akuntansi & Ekonomika, 2023)
Puskesmas with BLUD status are given flexibility in the context of managing health services, both from human resources (HR) to financial management. In Pekanbaru City there are 21 Community Health Centers with BLUD status. The sample in this study used a purposive random sampling method. The results of analytical testing of the influence of human resources on the quality of financial reports for regional public service agencies (BLUD). Namely the application of the local government accounting system to the quality of the financial reports of the regional public service agency. From the results of the third analytical test that has been carried out, it is known that organizational culture variables have a significant effect on the quality of the financial reports of the Regional Public Service Board (BLUD) of the Community Health Centers in Pekanbaru City. And it can be concluded that the three hypotheses are influential and significant